Analysis of burnout prevalence among German physicians working in a palliative care setting: a survey of the AIO quality of life working group - Herbrand, Lena; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter; Büttner, Sylvia; Haag, Georg Martin; Gencer, Deniz (Oncology research and treatment, 2024)
Introduction: Palliative care physicians (Pcps) face special challenges caring for terminally ill patients. We conducted this study to evaluate the burnout (bo) prevalence among pcps and sought to identify risk as well as protective factors as a basis for the development of preventive measures. Methods: Participants (Pcs) were invited via e-mail to complete an online survey between May and June 2022. Besides the Oldenburg Burnout Inventory assessing the bo dimensions of exhaustion (exh) and disengagement (dis), sociodemographic data were collected. Results: The study found that 58% (cut-off mean value [M] ≥2.18) or more specifically, 38% (cut-off M ≥2.5) of the pcs showed increased scores in the exh subscale as a key dimension of bo. All dimensions were correlated with the level of medical and palliative care training, with higher scores for physicians in training. Furthermore, pcs without preventive measures like employee appraisals at work were more likely to be considered exhausted, disengaged, or burned out. The discrepancy between high exh and low dis scores shows that the polled pcps, despite feeling exh, nevertheless considered their work meaningful. Conclusion: Bo prevalence among pcps exceeds that of the general population and other specialties, whereas inexperienced pcps might be at high risk of shifting from exh to bo and could therefore benefit from tailored support. Further preventive measures including individual and organizational aspects are necessary to prevent bo and promote health among medical staff, thereby preserving quality of patient care. Elementary preventive measures such as employee appraisals can have a protective effect against bo.
Gesehen am 19.07.2024